EFFECT OF CRUDE OIL AND BIOSTIMULANT (BIOREMEDIATION) ON GROWTH EXTRACT OF MAIZE (ZEA MAYS (L.) AND COWPEA (VIGNAUNGUICULATA (L.) WALP) - A.G., Iyagba; U.S., Offor (European Scientific Journal, ESJ, 2014)
The phytotoxic effects of crude oil concentration in soil on growth extracts – Relative growth rate (RGR), Relative leaf growth rate (RLGR), Leaf Area ratio (LAR) and Net Assimilation rate (NAR) of maize (Zea mays (L.) and cowpea (Vigna unguiculata (L.) Walp) was examined. The beneficial effects of bioremediation with addition of Biostimulant – Sawdust on the growth maize and cowpea in an oil contaminated soil was also determined. It was observed that crude oil contaminated soil (400ml) per plot was phytotoxic to both crops. In contrast, obvious phytotoxicity was observed in soils planted with maize. In addition, bioremediation with Sawdust reduced phytotoxicity and increase the growth indices of crops during the study.